2002
DOI: 10.1002/1521-3838(200208)21:3<239::aid-qsar239>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

CoMFA, CoMSIA and GRID/GOLPE studies on calcium entry blocking 1,4-dihydropyridines

Abstract: Three different 3D QSAR methods have been applied for a common pharmacophore model of 45 calcium antagonistically active 1,4-dihydropyridines (DHP) in order to find best correlation of interaction fields and biological activity. Analysis for the entire data set yielded r 2 /q 2 cv values in a range starting from 0.821/0.620 (GRID/ GOLPE) over 0.872/0.600 (CoMFA) to 0.908/0.744 (CoM-SIA). The robustness of these models was tested not only via leave-one-out but also by leave-9-out crossvalidations. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In particular, a study by Schleifer and Tot [42] aimed to apply and compare different methods for 3D-QSAR, such as GRID/GOLPE, CoMFA and COMSIA. The analysis of the set of 4-phenyl-substituted 1,4-DHPs indicated unfavourable steric interactions for bulky moieties in the para-position of the phenyl ring and favourable interactions for bulky substituents in ortho-and meta-positions.…”
Section: Analysis Of 14-dhp Structure-activity Relationships As Ltypmentioning
confidence: 99%
“…In particular, a study by Schleifer and Tot [42] aimed to apply and compare different methods for 3D-QSAR, such as GRID/GOLPE, CoMFA and COMSIA. The analysis of the set of 4-phenyl-substituted 1,4-DHPs indicated unfavourable steric interactions for bulky moieties in the para-position of the phenyl ring and favourable interactions for bulky substituents in ortho-and meta-positions.…”
Section: Analysis Of 14-dhp Structure-activity Relationships As Ltypmentioning
confidence: 99%
“…The basic chemical structure of these compounds is shown in Figure 1, and their biological activity is represented in Table 1. Earlier QSAR studies indicated that the biological activity of these compounds is controlled by the electronic, hydrophobic, and steric factors 41–49. To find a relation between calcium channel antagonist activity and the quantum chemical features of the chemicals, a wide set of quantum chemical descriptors were calculated by the ab initio method.…”
Section: Resultsmentioning
confidence: 99%
“…1). The biological activity of these compounds were previously reported by Cobrun et al41 This data set has been used by the others 45–49. In Table 1 the structural features and the biological activity of the DHP derivatives used in this study are represented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), the prototype of which is nifedipine, have been the aim of many SAR [6][7][8][9][10] and QSAR studies [11][12][13][14][15][16][17][18][19]. QSAR models are mathematical equations relating chemical structure to their biological activity.…”
Section: Introductionmentioning
confidence: 99%